Combined use of kaolin and bentonite molding clays - S. A. Kulikov; F. I. Rudnickij; V. A. Shumigaj (Литьë и металлургия, 2024)
The article compares the properties of kaolin and bentonite clays. It has been shown that kaolin clays have high fire resistance, and bentonites have high astringent properties. The experience of specialists from OJSC “MTW” in the joint use of various types of clays is considered. The combination of kaolin and bentonite in the suspension made it possible to increase the strength of the molding sand while maintaining moisture levels. The disadvantage of kaolin clay suspensions is that the moisture content increases with increasing dosage. When preparing bentonite suspensions, their short shelf life should be taken into account.